A study on the level of job satisfaction among nurses in KPJ Sabah Specialist Hospital / Adiza Idris and Erina Izzati Aneesa Ahmad Tahir - Idris, Adiza; Ahmad Tahir, Erina Izzati Aneesa (2015)
This paper is to study on the level of Job Satisfaction among nurses in KPJ Sabah Specialist Hospital. Job satisfaction is defined as a pleasurable feeling that result from the perception that one's job fulfills or allows the fulfillment of one's own job values in organization as the higher the job satisfaction, then the more likely employees will hold the positive attitude towards their jobs. The objective for this paper is to identify whether the reward system has a relationship with job satisfaction among the nurse in KPJ Sabah Specialist Hospital, to identify whether the working condition has a relationship with job satisfaction among the nurse in KPJ Sabah Specialist Hospital and to identify whether the supervision has a relationship with job satisfaction among the nurse in KPJ Sabah Specialist Hospital. The studies are focusing on 100 of nurse respondent in KPJ Sabah Specialist Hospital.